A NOVEL VALIDATION HPTLC METHOD FOR THE QUANTITATIVE DETERMINATION OF CLOFAZIMINE - VARUN RISHI KAPOOR; SHISHU (International Journal of Pharma and Bio Sciences, 2013)
A novel, highly sensitive high-performance thin-layer chromatography (HPTLC) method for analysis of clofazimine (CFZ) was developed and validated. Separation was achieved on aluminum plates pre-coated with silica gel 60 F254 using mobile phase toluene/ethyl acetate/methanol/glacial acetic acid (6:3:1:0.1, v/v/v/v) at room temperature (25 ± 2 ºC) for CFZ. The analytes were quantified spectrodensitometrically at 286 nm. The calibration curve was linear (r2 = 0.9974 ± 0.0012). Various parameters like limit of detection (LOD) and quantification (LOQ), accuracy (% DEV), precision (%RSD) and robustness of the quantification method were assessed. Also the method was employed to estimate drug levels in biological fluids and to study ex-vivo permeation profile of simple ointment of CFZ through rat skin. The method was found to be simple, rapid, accurate, reproducible, cost-effective and finds suitability in estimating drug levels in biological tissues and fluids and for routine analysis in bulk and pharmaceutical dosage forms. The primary advantage of the proposed procedures is the sensitivity, which surpasses the sensitivity of previously reported procedures